1985
DOI: 10.1056/nejm198504253121703
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Receptor Binding of Biologically Inactive Thyrotropin in Central Hypothyroidism

Abstract: Previous studies have suggested that certain cases of idiopathic central hypothyroidism of hypothalamic origin may result from the secretion of biologically inactive thyrotropin. To investigate this possibility and to define the mechanism of defective hormone action, we measured the adenylate cyclase-stimulating bioactivity (B) and receptor-binding (R) activity of purified immunoreactive serum thyrotropin (I) from seven patients with hypothalamic hypothyroidism. We found a strikingly decreased R/I ratio (less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
82
1
5

Year Published

1991
1991
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(94 citation statements)
references
References 29 publications
6
82
1
5
Order By: Relevance
“…There have been no patients with isolated TRH deficiency defined, but similar elevation has also been reported in some patients with central hypothyroidism (21). These patient's TSH activities were observed to be significantly reduced (22,23). Because the TRH Ϫ͞Ϫ mice showed the diminished thyroid hormone response to endogenous TSH after TRH stimulation, but normal response to exogenous TSH, it is concluded that the biological activity of circulating TSH in the TRH Ϫ͞Ϫ mice was attenuated.…”
Section: Discussionmentioning
confidence: 57%
“…There have been no patients with isolated TRH deficiency defined, but similar elevation has also been reported in some patients with central hypothyroidism (21). These patient's TSH activities were observed to be significantly reduced (22,23). Because the TRH Ϫ͞Ϫ mice showed the diminished thyroid hormone response to endogenous TSH after TRH stimulation, but normal response to exogenous TSH, it is concluded that the biological activity of circulating TSH in the TRH Ϫ͞Ϫ mice was attenuated.…”
Section: Discussionmentioning
confidence: 57%
“…Hormone resistance syndromes can be broadly defined as reduced or absent end-organ responsiveness to a hormone. Several general mechanisms have been identified, [37][38][39] and a quantitative reduction in receptor or defects in postreceptor signaling pathways seem to be the more probable explanations; but a different explanation may be plausible. A subset of depressed patients demonstrated a diminished TSH response to TRH stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that plasma TSH was increased in hypopituitarism due to biologically hypoactive TSH secretion [23], low capacity for binding to TSH receptor [24] and abnormality of the carbohydrate chain in the TSH molecule [25]. As glucocorticoid had a suppressive effect on TSH secretion [13], it may be considered that hyposecretion of glucocorticoid induced the increase in plasma TSH.…”
Section: Discussionmentioning
confidence: 99%